Green power / energy harvesting from wastage energy of human muscle activities - Dhar, Palash; Khandakar, Ajijul Hakim (BRAC University, 2013)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2013